Alliances in Industrial Purchasing: The Determinants of Joint Action in Buyer-Supplier Relationships - Heide, Jan B.; John, George (Journal of Marketing Research, 1990)
Recent trends in industrial markets indicate that buyers and sellers are increasingly supplanting conventional “arm's length” arrangements with “alliances” involving closer ties. The authors develop a theoretical model of industrial buyer-supplier ties that presents joint action as a key aspect of closeness. Whereas conventional ties emphasize a clearly defined division of labor, these newer relationships are distinguished by more tightly integrated roles based on undertaking activities jointly. Drawing primarily on a normative theory of transaction costs, the authors identify the conditions under which these relationships are useful. The utility of the relationships derives from an ability to safeguard relationship-specific investments and to facilitate adaptation to uncertainty. Using data from a sample of industrial firms and their suppliers, the authors test these predictions. The results show good support for the model. Consequences for research and practice in marketing are drawn.